Clinical features of cystic neutrophil granulomatous mastitis in 62 cases - Mengjie Wang; Dongxiao Zhang; Na Fu; Min Liu; Hongkai Zhang; Shuo Feng; Yifei Zeng; Wenjie Zhao; Jianchun Cui; Khattak Mazher Mansoor (Heliyon)
Background: Cystic neutrophilic granulomatous mastitis (CNGM) is a rare breast inflammatory condition. Despite its rarity, understanding its pathogenesis and clinical features is crucial for accurate diagnosis and effective management. This study delves into the characteristic of CNGM. Methods: In this meticulous investigation, we examined and analyzed the biological data, clinical features, ultrasound imaging, and histopathological morphological information of 62 patients diagnosed with CNGM through pathological examination. The study cohort was sourced from the Galactophore department of Beijing Hospital of Traditional Chinese Medicine from September 2019 to September 2022. Results: Sixty-two patients, with an average age of 33.30 years, were all female. Among the 62 patients, some patients had a history of oral psychotropic drugs, hyperprolactinemia, pituitary tumors, non-puerperal mastitis (NPM), and breast trauma history, or a family history of breast cancer. The primary clinical manifestations were characterized by pain and palpable masses, accompanied by redness, ulceration, nipple discharge, and nipple retraction. Additionally, systemic symptoms, such as fever, headache, erythema nodosum, and cough, were observed. Ultrasound examinations revealed predominantly hypoechoic masses, axillary lymphadenopathy, dilated ducts, and thickening breast glands. Histopathological analyses demonstrated the formation of lobular structural destruction, acute and chronic inflammatory cell infiltration, granulomas, and cystic vacuole. Gram staining revealed detection rates of 42 % for gram-positive bacteria and 11 % for gram-negative bacteria. Conclusion: This study highlights the occurrence of CNGM in women of childbearing age. Some patients have a history of NPM, hyperprolactinemia and breast trauma. The main symptoms of CNGM include breast lumps, redness, pain, and ulceration. Some patients possibly experiencing nipple discharge, nipple retraction, fever, and erythema nodosum. CNGM primarily manifests as poorly defined hypoechoic areas under ultrasound. Both gram-positive bacteria and gram-negative bacteria were detected by Gram staining.